45 Intravascular ultrasound guidance of percutaneous coronary interventions in ostial chronic total occlusions. (28th September 2016) - Ryan, N; Vedia-Cruz, O; Dingli, P; Salinas, P; Nombela-Franco, L; Nuñéz-Gil, I; Jiménez-Quevedo, P; Gonzalo, N; Fernandez-Ortiz, A; Escaned, J
Abstract : Background: Inability to cross the lesion with a guidewire is the most common reason for failure in percutaneous revascularisation (PCI) of chronic total occlusions (CTOs). An ostial or stumpless CTO is an acknowledged challenge for CTO recanalisation due to difficulty in successful wiring. IVUS imaging provides the opportunity to visualise the occluded vessel and to aid guidewire advancement. We review the value of this technique in a single-centre experience of CTO PCI. Methods: This series involves 22 patients who underwent CTO-PCI using IVUS guidance for stumpless CTO wiring at our institution. CTO operators with extensive IVUS experience in non-CTO cases carried out all procedures. Procedural and outcome data in this population was prospectively entered into the institutional database and a retrospective analysis of clinical, angiographic and technical data was performed. Results: 17 (77%) of the 22 procedures were successful. The mean age was 59.8 ± 11.5 years, and 90.9% were male. The most commonly attempted lesions were located in the Left Anterior Descending (LAD) 36.4% (8) and Circumflex artery (LCx) 31.8% (7). Mean JCTO score was 3.09 ± 0.75 (3.06 ± 0.68, 3.17 ± 0.98 in the successful and failed groups respectively p = 0.35). The mean contrast volume was 378.7 ml ± 114.7 (389.9 ml ± 130.5, 349.2 ml ± 52.2 p = 0.3 in the successful and failed groups respectively). There was no death, coronary artery bypass grafting or myocardial infarction requiring intervention in this series. When the success rates were analysed taking into account the date of adoption of this technique, the learning curve had no significant impact on CTO-PCI success. Conclusions: This series describes a good success rate in IVUS guided stumpless wiring of CTOs in consecutive patients with this complex anatomical scenario.